2011
DOI: 10.1007/s10120-011-0074-9
|View full text |Cite
|
Sign up to set email alerts
|

Multivisceral resection for gastric cancer: a systematic review

Abstract: Background The overall prognosis and survival of patients with advanced gastric cancer is generally poor. One of the most powerful predictors of outcomes in gastric cancer surgery is an R0 resection. However, the extent of the required surgical resection and the additional benefit of multivisceral resection (MVR) are controversial. Methods Electronic literature searches were conducted using Medline, EMBASE, and the Cochrane Central Register of Controlled Trials from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 15 publications
3
36
0
4
Order By: Relevance
“…Several systematic reviews were subsequently written on the basis of the results of this literature review. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Panelists were recruited through solicitation of nominations from the heads of surgical, medical, and radiation oncology units at all major cancer centers in North America, as well as corresponding authors of articles on clinical management of GC. From the applicants, a 16-member international, multidisciplinary panel of physicians with expertise in the care of GC was assembled, balancing practice type and geographic location, but with a focus on surgical representation ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several systematic reviews were subsequently written on the basis of the results of this literature review. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Panelists were recruited through solicitation of nominations from the heads of surgical, medical, and radiation oncology units at all major cancer centers in North America, as well as corresponding authors of articles on clinical management of GC. From the applicants, a 16-member international, multidisciplinary panel of physicians with expertise in the care of GC was assembled, balancing practice type and geographic location, but with a focus on surgical representation ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…First, although an extensive and rigorous review of the literature was provided to the panel, the majority of the data was gathered from retrospective studies. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Although scoring of scenarios reflect an individual's interpretation of the literature, as well as their personal experience treating GC, in areas where there is little evidence, the opinion of the experts becomes more influential. Second, our panel composition was heavily weighted to surgeons, and specifically to surgical oncologists, possibly influencing the outcome.…”
Section: Provider Considerationsmentioning
confidence: 98%
“…In a systematic review of 17 studies (including a total of 1343 patients), perioperative mortality was found to differ significantly, ranging from 0 to 15 %, and perioperative morbidity was similarly noted to be anywhere between 12 and 90 %. 7 Along the same lines, analyses of individual studies show some authors advocating that MVR for gastric cancer can be performed safely with a perioperative mortality rate of approximately 4 %, 3,[8][9][10] with others reporting perioperative mortality rates in the range of 10-13 %. 6,[11][12][13][14] This variability in results can be attributed in part to the effect of the ''learning curve'' for these challenging operations, as demonstrated in a study of 127 patients who underwent MVR for gastric cancer in Taiwan: when authors compared their results between the first 4 years and the last 8 years of their 12-year study period, they reported a decrease in the postoperative mortality from 17 to 1 %, and in the postoperative morbidity from 57 to 36 %.…”
mentioning
confidence: 96%
“…This type of multivisceral resections is already the standard of care for gastric and colon cancers with improved long-term outcomes and acceptable morbidity and mortality. 10,11 To our knowledge, this study is the largest single institution series of patients with extended distal pancreatectomy for adenocarcinoma of the pancreatic body/tail, although it includes only 93 patients. This study, however, presents several limitations.…”
Section: Commentsmentioning
confidence: 97%